Peningkatan Produksi dan Pemasaran Online Bunga Kering Rayung Gambas - Gunawan Budiyanto; Aris Slamet Widodo (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
Bluluk Gallery is one of the MSMEs engaged in the dried flower craft business initiated in 2006 after the Yogyakarta earthquake, located in Ngabean Hamlet, RT 03, Triharjo Village, Pandak District, Bantul Regency. This program is based on the condition of the Bluluk Gallery SMEs, which are still having production and marketing constraints due to the COVID-19 pandemic. This program aims to improve the production and marketing performance of the Bluluk Gallery SMEs' dried flower products. The program implementation was through socialization, training, and direct practice using the media. The results showed that the knowledge and skills of the Bluluk Gallery MSME managers have increased, which are implemented in the form of business management, production management, and online product marketing through digital marketing optimization.